Comprehensive Analysis of Minibuses Gravity Center: A Post-Production Review for Car Body Industry - Djoko Wahyu Karmiadji; Muchamad Gozali; Muji Setiyo; Thirunavukkarasu Raja; Tuessi Ari Purnomo (Universitas Muhammadiyah Magelang, 2021)
The center of gravity (CoG) on the minibus is one of the fundamental parameters that affect the operation of the vehicle to maintain traffic safety. CoG greatly affects vehicle maneuverability due to load transfer between the front and rear wheels, such as when turning, braking, and accelerating. Therefore, this research was conducted to evaluate the operational safety of minibuses produced by the domestic car body industry. The case study was conducted on a minibus with a capacity of 30 passengers to be used in a mining area. Investigations on CoG were carried out based on the minibus specification data, especially the dimensions and forces acting on the wheels. Minibuses as test objects were categorized in two conditions, namely without passengers and with 30 passengers. The test results are expressed in a coordinate system (x, y, z) which represents the longitudinal, lateral, and vertical distances to the center of the front wheel axle. CoG coordinate values without passengers are (2194.92; 7.11; 1327.97) mm and CoG coordinates with full passengers (30 people) are (2388.52; 13.04; 1251.72) mm. The test results show that the change in CoG at full load is not significant which indicates the minibus is safe when maneuvering under normal conditions.